Unsuccessful Osteochondral Allograft Cap to Prevent Overgrowth in a Pediatric Patient with Previous Transtibial Amputation: A Case Report. Issue 2 (24th April 2023) - Pluta, Natalia A.; Harrington, Colin J.; Smith, Douglas G.; Gantsoudes, George D.
Abstract : Case: This case demonstrates the attempted utilization of an osteochondral allograft for the prevention of bony overgrowth in a patient with fibular hemimelia and previous transtibial amputation with failure of Teflon capping. Additionally, we describe a novel technique to provide additional padding and increase the width of the residual limb using a dermal allograft. Conclusions: Bony overgrowth after pediatric amputations is common and often necessitates revision procedures secondary to infection, ulceration, pain, and discomfort with prosthesis use. Our use of an osteochondral allograft cap to prevent bony overgrowth ultimately failed 13 months following the procedure, and further research on various graft options and other treatment modalities is warranted, especially if the proximal fibula is unavailable or there is concern for donor site morbidity associated with harvesting autologous grafts.